Fault-Tree Analysis of Different Systems - Kumar, Ankush (My University, 2009)
This thesis is devoted to fault tree analysis of different systems, the qualitative and quantitative analysis of their fault trees. The fault tree analysis is a deductive failure based approach, where an undesired state of the system is specified and analyzed to find the ways in which the system can reach that state. The main topics are the introduction to fault tree analysis, qualitative and quantitative analysis of Computer System, Lathe Machine & Printing Circuit Board Assembly. The chapter-wise summary of the thesis is as follows: Chapter 1 is introductory in nature. This chapter includes basic definitions, operations and concepts used throughout the work. Chapter 2 presents brief review of the work done in the area of fault tree analysis, qualitative and quantitative analysis of fault tree. In Chapter 3, the basic reasons for the failure of computer system have been studied. Fault tree has been constructed on the basis of this study and qualitative and quantitative analysis has been done. In Chapter 4, the basic reasons for the failure of tool broken of the lathe machine has been studied. Fault tree has been constructed on the basis of this study and qualitative and quantitative analysis has been done. In the last chapter, the basic reasons for the failure of PCBA system have been studied. Fault tree has been constructed on the basis of this study and qualitative and quantitative analysis has been done.
M.Sc.(Maths and Computing)
Keywords: Fault Tree Analysis; PCBA System; Lathe Machine; Computer System